SISTEM PELAKSANAAN ATAS PENDAFTARAN TANAH BAGI MASYARAKAT EKONOMI LEMAH MELALUI PRONA DIKANTOR PERTAHANAN KOTA MEDAN - MARSINTA NAPITUPULU (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Muhd Yamin, SH, MS, CN2. Prof. Dr. Runtung, SH, MHum3. Prof Dr. Budiman Ginting, SH, MHumIn order to ensure legal certainty, especially in the field of land registration, the implementation of land registration can be done by individually and in mass or PRONA. The land registration is an obligation, both holders of land rights and the government. To reviewing matters mentioned above, this research is analytical descriptive and the approach methods are normative juridical and empirical, the research location is Medan Land Affairs Office North Sumatra, the sample selected by purposive sampling technique as many as 10 people on the land rights applicant's through PRONA. The land registration through PRONA as legal certainty is totally siding with the sense of justice and humanity, especially weak economy people in order to provide protection to the interests of the economically weak groups. It is suggested to the government to create a new mode of land registration so that can solve the barriers and achieve the goals for the land registration in order to goals aspired by UUPA and soon realized the land registration in Indonesia. Keywords: PRONA Land Registration, Weak Economy People